Lease of Agricultural Land in Public Ownership - Baturan, Luka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
This paper analyzes the legal norms which regulate leasing of agricultural land in public ownership. The basic hypothesis is that the main goal of land leasing should be to achieve an efficient allocation and maximization of public rental income. It was concluded that we should eliminate all restrictions that serve as barriers to market allocation. These include provisions thatrestrict some groups from participating in the land lease auctions, then the preemptive right of lease, as well as the ban on subleasing. It also criticizes the application of the principles of affectation, or restriction of freedom of local governments in the use of funds received from land leasing.